Моделирующие полиномы от N-переменных в машиностроении - Остерник, Э. С. (НТУ "ХПИ", 2010)
Розглянуто квадратичну апроксимацію дискретно заданої функції n-змінних за допомогою алгебраїчних поліномів. Доведено існування та єдиність найкращого у середньому квадратичному полінома. При постійному кроку аргументів матрицю системи нормальних рівнянь можна зробити квазідіагональною. Для ряду задач статики та динаміки, включаючи вібрацію турбогенератора, алгоритм реалізовано на ЕОМ.

The quadratic approximation of the discretely designed function of n-variables is analyzed using algebraic polynomials. The existence and uniqueness of the best polynomial in the quadratic mean has been proved. The matrix of the standard equations system may be made quasi-diagonal at the constant step of arguments. The algorithm used in a number of tasks of the statics and dynamics, including vibration of the turbogenerator, has been implemented on the basis of the electronic computer.
Keywords: динамика машин; прочность машин; алгебраические полиномы; квадратичные полиномы; квазидиагональные матрицы; конструктивная математика